2017
DOI: 10.1016/j.ahj.2017.08.011
|View full text |Cite
|
Sign up to set email alerts
|

International trends in clinical characteristics and oral anticoagulation treatment for patients with atrial fibrillation: Results from the GARFIELD-AF, ORBIT-AF I, and ORBIT-AF II registries

Abstract: Among new-onset AF patients, non-vitamin K antagonist oral anticoagulant use has increased and antiplatelet monotherapy has decreased. However, anticoagulation is used frequently in low-risk patients and inconsistently in those at high risk of stroke. Significant geographic variability in anticoagulation persists and represents an opportunity for improvement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
109
2
9

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(133 citation statements)
references
References 18 publications
13
109
2
9
Order By: Relevance
“…However, warfarin remains to be used widely in the developing countries due to its documented effectiveness and low acquisition cost. [2][3][4] Several pharmacoeconomic studies suggested that, at current price, NOACs are still not cost-effective in developing countries. 5,6 In addition, there are other indications where NOACs have not been shown to be able to replace warfarin, most importantly, for stroke prevention in patients with mechanical heart valve replacement (SPMVR).…”
Section: Introductionmentioning
confidence: 99%
“…However, warfarin remains to be used widely in the developing countries due to its documented effectiveness and low acquisition cost. [2][3][4] Several pharmacoeconomic studies suggested that, at current price, NOACs are still not cost-effective in developing countries. 5,6 In addition, there are other indications where NOACs have not been shown to be able to replace warfarin, most importantly, for stroke prevention in patients with mechanical heart valve replacement (SPMVR).…”
Section: Introductionmentioning
confidence: 99%
“…Полученные данные подтверждают результаты ряда крупных международных регистровых исследований и работ отечественных авторов о недостаточной частоте назначения ОАК у больных с ФП в реальной клинической практике [7][8][9][10][11][12][13][14][15][16][17][24][25], хотя следует отметить, что частота назначения ОАК при ФП по данным ряда международных регистров существенно выше, чем в РФ, и составляет в странах Западной Европы 60%-80% [12][13][14][15][16][17].…”
Section: Discussionunclassified
“…По данным ряда регистров больных с ФП антикоагулянтная терапия, в т.ч. варфарином и НОАК, в медицинской практике назначается недостаточно часто, что не соответствует в должной степени клиническим рекомендациям [11][12][13][14][15][16][17]. Результаты регистров РЕКВАЗА и РЕКВАЗА ФП о медикаментозном лечении больных с ФП в медицинской практике были опубликованы ранее [18][19][20][21][22].…”
Section: терапия оральными антикоагулянтами у больных с фибрилляцией unclassified
“…2 Considering the prevalence of atrial fibrillation (AF), there may be at least 615 000 extremely obese adults with atrial fibrillation in the US. 3 As 67%-88% of AF patients are on anticoagulation, 4 this suggests that at least 500 000 extremely obese individuals in the US with AF have an indication for, or are being treated with, anticoagulation. Similar calculations can be performed for venous thromboembolism (VTE): the Centers for Disease Control (CDC) estimate that as many as 900 000 people in the US could be affected by VTE, 5 most of whom will require anticoagulation for some period of time.…”
Section: Prevalence Of Extreme Obesitymentioning
confidence: 99%